TEKTONIK DAN JALUR VULKANIK BUSUR BELAKANG BAWEANMURIA SEBAGAI PENGONTROL PEMBENTUKAN CEKUNGAN PATI DAN POTENSI HIDROKARBON - Ediar Usman (Indonesian Journal of Applied Sciences, 2012)
are situated on the southeast border of the granite chalk belt of L. Jawa, and increasingly far from the recent subduction. From interpretation of seismic data of Pre-Tertiary rocks and Palaeogene and Neogene sediment, a tectonic direction was obtained, of the same direction as the Muria – Bawean back arc volcanic belt, namely Southwest – Northeast, or what is known as Pola Meratus. The development of the Palaeogene and Neogene tectonic in line with the aforementioned Plistosen-Holosen volcanic belt, points to the research area as an unstable tectonic and volcanically active from Palaeogene to Holosen. Other evidence of the Muria – Bawean back arc volcanic belt is the chemical composition of the five volcanic rock samples in area G. Muria shows genesis of Calc-Alkaline-Shoshonite magma. Total alkaline content is roughly between 3,08 - 13,92% including in the Andesit – Dasit group, and SiO2 is between 59 – 69,82% characterised medium-acidic. Results of microscopic analysis of the five rock samples show plagioclase mineral content, K-feldspar, hornblende, firoksen and glass dominant in all samples. Fomation of the aforementioned Palaeogene-Neogene (Pola Meratus) tectonic and Muria – Bawean back arc volcanic belt split the East JavaNorth basin in two, namely Pati Basin in the West and East Java North Basin in te East. The aforementioned tectonic and volcanic influence caused sub-basin orientation at Pati Basin and the East Java North Basin heading Southwest – Northeast. This condition has led to a new understanding of basin formatin and sub-basin orientation. Basic formation of a basin and sub-basin is not only based on the process of Palaeogene geology, but influenced by Neogene volcanism and tectonics. Similarities in the tectonic, volcanic and historical process of the formation of Pati Basin and the East Java North Basin show that the two basins have a petroleum system and the same prospectively high hydrocarbon content, so that if a more detailed exploration of Pati Basin is undertaken, it is predicted that hydrocarbon will be obtainable, as at the East Java North Basin, which is currently in production.